Technological Evaluation of Kera ice Cream - Geevarghese P I (Department of Dairy Science, College of Veterinary and Animal Sciences, 1996)
An experiment was conducted to assess the suitability of incorporating coconut fat in the form of coconut cream in preparing ice cream and ice cream mix powder replacing milk fat at 25, 50, 75 and 100 per cent levels (treatments) so as to reduce the cost of preparation of ice cream. The product developed was named as kera ice cream and the qualities were compared with normal ice cream (control). Kera ice cream was prepared with pineapple flavour and a combination of sodium alginate and glyceryl monosterate as stabilizer since it was found to be the most suitable. It was found that replacement of milk fat with coconut fat at any level does not influence the acidity, pH and specific gravity of kera ice cream mix. The relative viscosity of kera ice cream was increased as fat substitution level increased. Higher surface tension was observed for the control, and among treatments it showed a gradual increase as replacement level increased. It was observed that the overrun percentage increased as replacement with coconut fat increased. Contrary to this a decreasing trend in meltdown time was observed as percentage replacement with coconut fat increased. Whipping ability was lowest for the control during the first 5 min of freezing but it significantly increased during the second five min of freezing. Structural details of the ice cream revealed that as replacement level increased the air cell diameter and cell wall thickness increased. Organoleptic quality of kera ice cream were comparable to normal ice cream. The savings in cost of production for kera ice cream with 100 per cent replacement was calculated as 40.57 per cent compared to control. The properties of the reconstituted ice cream revealed more or less similar trend in characters like acidity, pH, specific gravity, overrun, meltdown time and organoleptic properties as that of the freshly prepared ice cream. The ultra structure of the kera ice cream mix powder particle were studied and it revealed that as replacement level increased the particle size also increased. Clumping of the particles and irregular surface were more evident at 75 and 100 per cent level whereas particles of the control and 25 per cent had smooth surface. Solubility index of the powder increased as percentage replacement increased. Significant difference could be noted with regard to bulk density and percent volume occupied by the powder particle. Storage studies were conducted with different packaging material and metallised polyester polyethylene was found to be the best. The moisture and titratable acidity of kera ice cream mix powder with and without antioxidant were significantly higher at any replacement level at 180 days of storage. The thiobarbituric acid value showed a significant difference for the powder without antioxidant at 120 days of storage and with antioxidant the difference could be noted at 180 days of storage. Peroxide value was recorded as zero at different periods of storage upto 180 days of storage. At 180 days of storage, powder without BHA at any replacement level showed significant difference whereas in antioxidant added powder difference could be noted at 75 and 100 per cent replacement levels. Nutritional qualities of kera ice cream was evaluated by rat feeding trials and was found that protein efficiency value and feed efficiency were comparable to ice cream diet. The cholesterol and triglyceride level in animals fed with kera ice cream and ice cream were also not different. Pathological examination of carcases and tissues of animals under treatment and control groups did not reveal significant changes indicating that incorporation of coconut fat cannot cause any untoward effect in organs and tissues of animals. It can be concluded that coconut fat can be incorporated in the prepartation of ice cream and mix powder with out any noticeable changes in the quality. Addition of antioxidant prolongs the keeping quality of the powder by two months. There is no health hazard in consuming the kera ice cream as revealed by the pathological examination of tissues from the experimental animals fed with kera ice cream.